2011
DOI: 10.1111/j.1540-8159.2011.03258.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Seattle Heart Failure Model in Patients on Cardiac Resynchronization Therapy

Abstract: The SHFM successfully stratifies HF patients on CRT/CRT-D and can be reliably applied to help clinicians in predicting survival in this clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(41 reference statements)
1
8
0
1
Order By: Relevance
“…Perrota et al 27 Validation SHFM n/a n/a n/a n/a H-L test: P>0.2 at 1, 2, and 3 y At 1 y=0.70 (0.61-0.79)…”
Section: Seattle Heart Failure Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Perrota et al 27 Validation SHFM n/a n/a n/a n/a H-L test: P>0.2 at 1, 2, and 3 y At 1 y=0.70 (0.61-0.79)…”
Section: Seattle Heart Failure Modelmentioning
confidence: 99%
“…The SHFM has been validated in 14 independent cohorts including 16 057 patients with HF (4 cohorts including 8983 patients with HF were selected from randomized controlled trials [ Table II in the online-only Data Supplement]). 11,18,[22][23][24][25][26][27][28] The validation cohorts involve diverse populations with a mean age from 52 to 77 years, a higher proportion of males (61%-82%), and mean LVEF between 17% and 45%. In 4 cohorts, the used of β-blockers was 20% to 35%, and in the remaining cohorts was >60% (maximum of 92%).…”
Section: Seattle Heart Failure Modelmentioning
confidence: 99%
“…A net underestimation of absolute risk calculated with the SHFM was observed among patients with an implanted device. More recently, Perrotta et al . reported that, in a mixed CRT population (CRT‐D, 263 patients; CRT‐P, 79 patients) with moderate to severe HF, the performance of the SHFM was good in predicting short‐, intermediate and long‐term survival, with Harrell c‐statistics ranging between 0.69 (1 year) and 0.70 (2 and 5 years).…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the SHFM in advanced HF patients referred for cardiac transplantation who were racially diverse and receiving optimal contemporary therapy has been recently tested; in this cohort, it was shown that in terms of absolute risk, SHFM systematically overestimated survival and underestimated risk, an effect more pronounced among patients with implanted devices. Little is known about the performance of the SHFM in CRT patients, particularly considering device type and more recent CRT recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…age and cause of heart failure), disease severity and duration of follow-up. [14][15][16][17][18][19][20] However, as the accuracy of the prediction degrades from the sample in which the system was first developed to subsequent application, 21 it requires to be validated before application in new patients.…”
Section: Introductionmentioning
confidence: 99%